PERNIKAHAN MENGGUNAKAN HITUNGAN WETON DI DESA SIDODADI GEDANGAN MALANG:: KAJIAN PERSPEKTIF KITAB FAR?`IDL AL-BAHIYYAH - Bahrul Ulum (LP3M IAI Al-Qolam, 2021)
This is a study of the practice of the weton of the marriage tradition in Sidodadi Village, to find out the views of the Sidodadi community about the weton tradition in marriage and, to find out the perspective of Islamic law on the weton tradition in the marriage of the Sidodadi community. This is a field research using qualitative methods, based on anthropological legal research. The data collection techniques used were interviews, observations, literature studies, and documentation studies after which the data were analyzed. The results of the study indicate that there are still many, and possibly all, people of Sidodadi Village who practice the weton tradition in marriage. The practice of the weton tradition in marriage is to determine matchmaking and determine the day of the wedding. Although the people of Sidodadi Village have different views about the weton tradition in marriage; there are those who agree and some who do not agree, the tradition of weton in this marriage is still firmly held and carried out to this day as a form of respect for the ancestors. The weton tradition in marriage does not conflict with Islamic law, because this tradition is merely an effort and prudence in determining matchmaking and wedding days, to get good luck while navigating domestic life. And the weton tradition in this marriage in the book of al-Far?`idl al-Bahiyyah is categorized as 'urf which is valid.